Penerapan Terapi Aromaterapi Jahe Roll-On untuk Mengurangi Mual dan Muntah pada Ibu Hamil di Klinik H. Syahruddin Tanjung Balai - Meiastrinara, Kindi; Sari, Selvi Puspan; Anggriani, Ririn (Jurnal Masyarakat Indonesia (Jumas), 2025)
Background: Emesis gravidarum is a common complaint during the first trimester of pregnancy. If left untreated, this condition can negatively impact the health of the mother and fetus. Ginger essential oil contains gingerol and shogaol, which are known to have antiemetic properties. Its roll-on form offers a practical and effective application method. Objective: To determine the effectiveness of ginger essential oil in roll-on form in reducing the frequency of nausea and vomiting in pregnant women at the H. Syahruddin Clinic, Tanjung Balai. A total of 20 pregnant women experiencing nausea and vomiting participated in this counseling session. Conclusion: Ginger essential oil in roll-on form has been shown to be effective in reducing nausea and vomiting in pregnant women and is a safe and practical non-pharmacological therapy option.